Ewing sarcoma of the small bowel: a study of seven cases, including one with the uncommonly reported EWSR1–FEV translocation. Issue 7 (25th February 2014) - Milione, Massimo; Gasparini, Patrizia; Sozzi, Gabriella; Mazzaferro, Vincenzo; Ferrari, Andrea; Casali, Paolo G; Perrone, Federica; Tamborini, Elena; Pellegrinelli, Alessio; Gherardi, Giorgio; Arrigoni, Gianluigi; Collini, Paola; et al.
<x xml:space="preserve">Abstract</x> Aims Primary Ewing sarcoma of the ileum has rarely been documented. Little is known about its pathogenesis and clinical implications, and it would be helpful to identify novel molecular markers. EWSR1–FEV translocation is exceedingly rare in Ewing sarcoma, as FEV expression is restricted to prostate, brain and serotonin neuroendocrine cells (NE) and related tumours. Methods and Results Paraffin sections or snap‐frozen material were used in this investigation. Tumours were investigated by means of immunohistochemistry, RT–PCR (EWSR1–FLI1, EWSR1–ERG and EWSR1–FEV transcripts), FISH analysis (EWSR1 break‐apart and specific EWSR1–FEV translocation) and spectral karyotyping (SKY). Ten ileal neuroendocrine tumours (INET) made up the control group for EWSR1–FEV translocation. Among 445 Ewing sarcomas cases spanning a period of 20 years, seven (1.6%) arose in the ileum. All tumours were immunoreactive for synaptophysin, CD99, FLI1 and vimentin. FISH identified EWSR1 rearrangement in all cases, with EWSR1–FLI1 transcripts being detected in all but one tumour showing the uncommon EWSR1–FEV rearrangement, with SKY, RT–PCR and FISH confirmation. The mean survival of EWSR1–FLI1 patients was 14 months, whereas the EWSR1–FEV patient was alive after 15 years despite several recurrences controlled by surgery alone. No INET showed EWSR1 translocation. Conclusions Most primary Ewing sarcomas of the ileum show the common EWSR1–FLI1 translocation, but EWSR1–FEV could be specific for tumours arising in the ileum and showing better prognosis.